Uranium, Mining and Hydrogeology 2008
DOI: 10.1007/978-3-540-87746-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Iron (Fe0) for Better Drinking Water in Rural Areas of Developing Countries

Abstract: Abstract. Many of the reasons behind the anthropogenic contamination problems in rural environments of developing countries lie in changes in the traditional way of life and the ignorance on the toxic potential of introduced manufactured products. A generalization trend exists within the international community suggesting that water in developing countries is of poor quality. However, the water quality is rarely analytically determined. Existing potabilization solutions may be prohibitively expensive for the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This communication is part of an ongoing effort for low‐cost water treatment using well‐design Fe 0 beds 5, 6, 17, 24–26, 70, 71. While dual filters of Fe 0 and quartz will be long‐term permeable, the substitution of Fe 0 by bimetallic materials or the substitution of inert sand by reactive metal oxides will sustain long‐term reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…This communication is part of an ongoing effort for low‐cost water treatment using well‐design Fe 0 beds 5, 6, 17, 24–26, 70, 71. While dual filters of Fe 0 and quartz will be long‐term permeable, the substitution of Fe 0 by bimetallic materials or the substitution of inert sand by reactive metal oxides will sustain long‐term reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the variability of the influents, the system outputs must be satisfactory. Based on state of the art knowledge of the mechanism of contaminant removal by Fe 0 /H2O systems, the use of metallic iron as a universal material for safe drinking water has been suggested [55,56]. The works of Ngai et al [18] suggested that the amount of Fe 0 in the filter is not necessarily high (e. g., 10% weight).…”
Section: /Sand Filtersmentioning
confidence: 99%
“…This conclusion is supported by the observation that even bacteria (Hussam and Munir, 2007;Diao and Yao, 2009) and viruses (You et al, 2005) are successfully removed in Fe 0 /H 2 O systems. The latter observation has led to the suggestion of metallic iron as a universal filter material in small above-ground walls and household filters for treatment of waters of unknown quality (Noubactep and Woafo, 2008;Noubactep et al, 2009b;Noubactep and Schöner, 2010b). If successfully developed, this simple idea could enable universal access to safe drinking water in remote areas around the world.…”
mentioning
confidence: 99%